No good fit: why the fitting attitude analysis of value fails - Bykvist, K (Oxford University Press, 2009)
Understanding value in terms of fitting attitudes is all the rage these days. According to this fitting attitude analysis of value (FA-analysis for short) what is good is what it is fitting to favour in some sense. Many aspects of the FA-analysis have been discussed. In particular, a lot of discussion has been concerned with the wrong-reason objection: it can be fitting to have an attitude towards something for reasons that have nothing to do with the value the thing has in itself. Much less attention has been paid to the problem of identifying the relevant attitudes in virtue of which value is supposed to be defined. An old complaint, however, is that the FA-analysis is bound to be circular, because the fitting attitude is best seen as an evaluative judgement or an evaluative experience. In this paper, I am arguing that the challenge to find a non-circular account is deepened by the fact that on many popular non-evaluative understandings of favouring, there are good states of affairs tha it is never fitting to favour, because it is logically impossible or irrational to favour them. I will also show that the remaining candidate of favouring, 'imaginative emotional feeling', will generate a new version of the wrong-reason objection if it is put to use in the FA-account. I shall conclude that the prospects of finding a non-circular FA-analysis look bleak.